Strength and Acid Resistance of M50 Grade Self-Compacting Concrete - Raj, D. V. Prudhvi; A. Mounika, A. Mounika; Naik, S. Balaji Manikanta; L. Maneesha, L. Maneesha; Priya, Y. Chandana; A. Fayaz, A. Fayaz (Journal of Neonatal Surgery, 2025)
Self-compacting concrete have very high strength and durability and is a fluid mixture of high performance, which is applicable in placing at difficult condition and without any vibrator in the structures with congested reinforcement. Sufficient powder along with a super plasticizer is used to make Self compacting concrete in order to flow it while the coarse aggregate are kept in a vicious suspension.M50 grade self-compacting concrete is developed using fly ash and rice husk ash which are industrial by products. The flow and strength properties of SCC in comparison with conventional concrete are investigated. Concrete is susceptibility to acid (such as nitric acid, hydrochloric acid and acetic acid) attacks because of its alkaline nature. Acid Durability Loss Factor is used to study the loss of strength, stability and weight of SCC in the influence of acid. This factor gives the performance of both strength and durability.